2022
DOI: 10.3390/languages7030180
|View full text |Cite
|
Sign up to set email alerts
|

Language Competence in Italian Heritage Speakers: The Contribution of Clitic Pronouns and Nonword Repetition

Abstract: The linguistic profile of bilingual children is known to show areas of overlap with that of children affected by Developmental Language Disorder (DLD), creating a need to differentiate the profiles and provide clinicians with tools to evaluate bilingual speakers in both of their languages. Data from typical adult bilinguals provide a picture of the language of a bilingual speaker at the end of language development. The present work explores how clitic production and nonword repetition (NWR) behave in mature la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…bilinguals, particularly when the two languages spoken are a clitic and a non-clitic language (Belletti et al, 2007;Romano, 2020Romano, , 2021Smith et al, 2022). The study by Smith et al (2023) provides the original dataset used also in the current study, found a differential pattern of clitic production across three groups (monolinguals, attriters, heritage speakers) where all types of clitics (one argument, as in 3 above, or clitic clusters) were significantly fewer in attriters compared to monolinguals, and in heritage speakers compared to attriters.…”
Section: Questionmentioning
confidence: 70%
See 4 more Smart Citations
“…bilinguals, particularly when the two languages spoken are a clitic and a non-clitic language (Belletti et al, 2007;Romano, 2020Romano, , 2021Smith et al, 2022). The study by Smith et al (2023) provides the original dataset used also in the current study, found a differential pattern of clitic production across three groups (monolinguals, attriters, heritage speakers) where all types of clitics (one argument, as in 3 above, or clitic clusters) were significantly fewer in attriters compared to monolinguals, and in heritage speakers compared to attriters.…”
Section: Questionmentioning
confidence: 70%
“…bilinguals, particularly when the two languages spoken are a clitic and a non-clitic language (Belletti et al, 2007;Romano, 2020Romano, , 2021Smith et al, 2022). The study by Smith et al (2023) provides the original dataset used also in the current study, found a differential pattern of clitic production across three groups (monolinguals, attriters, heritage speakers) where all types of clitics (one argument, as in 3 above, or clitic clusters) were significantly fewer in attriters compared to monolinguals, and in heritage speakers compared to attriters. This phenomenon was interpreted as a by-product of "inter-generational attrition", where only monolinguals retain a strong preference for clitics over any other structure, attriters make use of single clitics but not of clusters and heritage speakers, whose input is provided by attriters, mostly prefer the use of lexical expressions.…”
Section: Questionmentioning
confidence: 70%
See 3 more Smart Citations